2009
DOI: 10.1152/ajpheart.01150.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent impairment of cardiac action potential conduction in type 1 diabetic rats

Abstract: The incidence of diabetes mellitus is increasing. Cardiac dysfunction often develops, resulting in diverse arrhythmias. These arise from ion channel remodeling or from altered speed and pattern of impulse propagation. Few studies have investigated impulse propagation in the diabetic heart. We previously showed a reduced conduction reserve in the diabetic heart, with associated changes in intercellular gap junctions. The present study investigated whether these effects are sex specific. Hearts from control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
0
16
1
Order By: Relevance
“…25,34 Contrary to our initial working hypothesis, the simulations showed that while reduced intercellular coupling does reduce overall CV, it does so without altering the slope of the CV vs. [K + ] o relationship. While the increased response to heptanol application in diabetic hearts appears to be clearly related to reduced intercellular coupling (above), it therefore appears that there may be an additional ''defect'' related to conduction in diabetic hearts.…”
Section: Response To Reduced Excitabilitycontrasting
confidence: 85%
See 4 more Smart Citations
“…25,34 Contrary to our initial working hypothesis, the simulations showed that while reduced intercellular coupling does reduce overall CV, it does so without altering the slope of the CV vs. [K + ] o relationship. While the increased response to heptanol application in diabetic hearts appears to be clearly related to reduced intercellular coupling (above), it therefore appears that there may be an additional ''defect'' related to conduction in diabetic hearts.…”
Section: Response To Reduced Excitabilitycontrasting
confidence: 85%
“…25,34 This was evident as a larger slowing of conduction velocity in the diabetic hearts than in controls in response to either (1) administration of the gap junction uncoupler heptanol or (2) increasing extracellular [K + ] ([K + ] o ) to reduce cellular excitability. Based on immunohistochemistry observations, our working hypothesis is that intercellular electrical coupling in the diabetic heart is compromised due to lateralization of Cx43, rendering the lateralized Cx43 non-functional.…”
Section: We Have Previously Published Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations